Structural and spectroscopic characterization of the second polymorph of 1-methylhydantoin - Nogueira, Bernardo A.; Henriques, Marta S. C.; Paixao, Jose Antonio; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
In a previous study [Nogueira, B.A.; Ildiz, G.O.; Canotilho, J.; Eusebio, M. E. S.; Fausto, R. J. Phys. Chem. A, 2014, 118, 5994-6008], two different polymorphs of 1-methylhydantoin (1-MH, C4H6N2O2) were identified using infrared spectroscopy, differential scanning calorimetry and polarized-light thermal microscopy. Unfortunately, at that time it was not possible to structurally characterize in detail the second polymorph (polymorph II) of the compound, due to lack of suitable crystals for X-ray diffraction structure determination. In this article, a throughout investigation of the polymorphism of 1-MH is presented. Screening for polymorphs was performed by recrystallization from different solvents, and the structure of polymorph II was determined for the first time by single crystal X-ray diffraction. The spectroscopic characterization of this polymorph was also undertaken, by Raman spectroscopy, which was also used to follow the phase transition between the two polymorphs (the well-known polymorph I, and the newly described polymorph II), showing that even though their structures are significantly distinct, the transition is a non-destructive one. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 1-Methylhydantoin; Polymorphism; Raman spectroscopy; X-ray diffraction; Hydantoins; Inhibitors; Spectra